Optical Properties of Berry Epicuticular Waxes in Four Georgian Grape Cultivars (Vitis vinifera L.) - Rustioni, L.; Maghradze, D.; Failla, O. (South African Journal of Enology and Viticulture, 2016)
The epidermis of plant shoot organs is generally covered by epicuticular waxes. The role of this layer is related mainly to the protection of the inner tissues from biotic and abiotic stresses. In this study, attention is focused on the optical properties of the berry epicuticular waxes of the grapevine (Vitis vinifera L.) at fruit ripening. The reflectance of the berry surface was measured before and after chloroform treatments in four Georgian grape cultivars grown in northern Italy. Epicarp optical properties were underlined at different wavelengths (341 to 1025 nm) for each cultivar. The results show that the berry waxes have several optical properties; it is possible that their main eco-physiological effect is to provide specific protection against different types of radiation. Besides the physiological aspects, the results are interesting also from a technical point of view in the field of interpretation of reflectance measurements carried out by non-invasive instruments.